The Challenge of School Governance: Role of Elementary School Committees in School Governance at Banyumas - Faozanudin, Muslih; Sri Sulistiani, Lilis (KnE Social Sciences, 2023)
This study aimed to explore the challenges of school committees (SC) associated with participating in school governance, especially in elementary schools. SCs have a strategic role in participating in advancing education at the elementary level and for accountability for the implementation of school programs and activities. However, not all SCs have not been able to carry out their role as strategic partners for the development of primary school governance. This study used a qualitative approach in which the researchers collected data from the results of in-depth interviews and focused-group discussions (FGD). The FGD was used to enable the researcher to consider the investigation from the perspective of the interviewees. This approach also enabled the informant to involve more deeply in an in-depth study of the duties and functions of the SC in the selected schools. The research findings showed that some patterns of relationships exist between the SC and school management. The better the relationship pattern between the two institutions, the more optimal the role of the SC tends to be. On the other hand, the committee’s role is ineffective when the relationship pattern is less balanced and harmonious. The study concludes that to encourage the active involvement of parents in the education of their children at the community level, school administrators and committee members need to be continuously encouraged and empowered through continuous training and intensive communication between principals. Keywords: accountability, School Committee, governance